PENGGUNAAN MEDIA BOOKLET DALAM UPAYA DETEKSI KETERLAMBATAN PERKEMBANGAN BALITA OLEH KADER KESEHATAN DAN GURU PAUD DI WILAYAH PUSKESMAS ALALAK TENGAH KECAMATAN BANJARMASIN UTARA TAHUN 2021 - Hapisah Hapisah; Rusmilawaty Rusmilawaty; Rafidah Rafidah (Jurnal Bakti untuk Negeri, 2022)
Almost 80% of screening for developmental delays is carried out in the Puskesmas area of ??North Banjarmasin District, which is carried out by health workers at the time of the toddler's to get immunizations and the rest is obtained at the posyandu based on oral information from health cadres and is already in a state of deviation. This also happens in PAUD, the teacher will report a developmental delay if the child has experienced developmental deviations. This situation shows that health cadres and PAUD teachers need additional information on how to carry out early detection of under-five development using KPSP. Objectives To provide training on how to fill out the KPSP booklet for health cadres and PAUD teachers and to practice how to assess child development according to age using the KPSP booklet for health cadres and Kindergarten teachers. The method used is counseling and the practice of using booklets. The results of community service were found that most of them had less knowledge before health education, and most of them had good knowledge after being given health education. The evaluation of early detection of development using the KPSP Booklet is mostly in the advanced category as many as 73.3%.